2021
DOI: 10.1108/jfc-02-2021-0045
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance challenges and opportunities in mitigating corporate fraud in Malaysia

Abstract: Purpose This study aims to examine the relationship between corporate governance and the likelihood of corporate fraud in Malaysia. Design/methodology/approach The sample of fraudulent companies in this study is the public listed companies that were charged with furnishing false statements to the Securities Commission of Malaysia and Bursa Malaysia Securities Berhad and was listed in the Malaysian Securities Commission Enforcement Release from the year 2000 to 2016. The non-fraudulent companies, which are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 65 publications
1
15
0
4
Order By: Relevance
“…Menurut data, rata-rata dewan komisaris independen dalam perusahaan observation sebesar 39,47 persen. Lebih lanjut, eksistensi independensi dalam dewan mungkin karena taat kepada aturan pemerintah untuk keberadaan dewan komisaris independen (Girau et al, 2021).…”
Section: Dewan Komisaris Independenunclassified
“…Menurut data, rata-rata dewan komisaris independen dalam perusahaan observation sebesar 39,47 persen. Lebih lanjut, eksistensi independensi dalam dewan mungkin karena taat kepada aturan pemerintah untuk keberadaan dewan komisaris independen (Girau et al, 2021).…”
Section: Dewan Komisaris Independenunclassified
“…Mekanisme corporate governance dapat digunakan oleh perusahaan untuk menyelaraskan kepentingan pemilik dan manajemen serta diperlukan sebagai sarana dalam melakukan pemantauan, pengendalian, dan pengelolaan untuk meminimalisir terjadinya fraud dalam laporan keuangan (Pamungkas et al, 2018). Corporate governance yang lemah sering dinilai sebagai bentuk peluang bagi perusahaan dalam melakukan kecurangan (Girau et al, 2022). Dewan komisaris (Board of Commisioner), Komisaris Independen (Independent Commisioner), Kepemilikan Institusional (Institutional Owneship) dan Komite Audit (Audit Committee) merupakan mekanisme corporate governance yang dapat mencegah fraud (Pramono Sari et al, 2020).…”
Section: Pendahuluanunclassified
“…Corporate governance yang lemah sering dinilai sebagai bentuk peluang bagi perusahaan dalam melakukan kecurangan (A. Girau et al, 2022). Dewan komisaris, Komisaris Independen, dan Kepemilikan Institusional merupakan mekanisme corporate governance yang dapat mencegah fraud (Pamungkas et al, 2018).…”
Section: Mekanisme Corporate Governanceunclassified
“…Under any circumstances when an individual’s heart wishes to attempt anything wrong it is the fundamental integrity which plays the role (Arens, 2012). The greater level of mismanagement has been observed in employees who have less integrity (Girau et al , 2021). The organisations that have worked with integrity will improve performance at work and will always promote the best employees to work with less supervision as stated in the Global Fraud Survey 2018.…”
Section: Extension Of Fraud Triangle Theory To Fraud Square – Propose...mentioning
confidence: 99%
“…Most of the anti-fraud experts suggested that anti-fraud ethics trainings and incentives to employees would help organisations to develop the sense of integrity in them and not get indulged in any wrongful or criminal activities in the organisations (Kochar and Saluja, 2020). However, it is suggested to the organisation’s management, employees and auditors to consider all the elements while detecting a fraud in an organisation (Girau et al , 2021).…”
Section: Extension Of Fraud Triangle Theory To Fraud Square – Propose...mentioning
confidence: 99%